Managerial economics for dummies - Graham, Robert J.
Does the study of Managerial Economics make your head spin? Relax! This hands-on, friendly guide helps you make sense of complex business concepts and explains to you in plain English how Managerial Economics enhances analytical skills, assists in rational configuration, and aids in problem-solving. "Managerial Economics For Dummies" gives you a better understanding of all the major concepts you'll encounter in the classroom: supply and demand, elasticity, decision-making, quantitative analysis of business situations, risk analysis, production analysis, pricing analysis, capital budgeting, critical thinking skills, and much more. Tracks to a typical Managerial Economics course Includes easy-to-understand explanations and examples Serves as a valuable classroom supplement